Singletons in a PLC at Work® Navigating on-Ramps to Meaningful Collaboration. - Leane, Brig (Solution Tree, 2022)
"Collaboration is a foundational practice in the professional learning community (PLC) process. Most teachers will collaborate in grade-level or course-alike teams in a PLC, but what about singletons-those teachers who do not have grade-level or course-alike peers? In Singletons in a PLC at Work: Navigating On-Ramps to Meaningful Collaboration, authors Brig Leane and Jon Yost help singletons find meaningful collaboration no matter what context they find themselves in. The book introduces three specific entry points (on-ramps) into meaningful collaboration for singletons-(1) the course-alike entry point (the virtual team), (2) the common-content entry point, and (3) the critical-friend entry point-as well as specific strategies to lay the groundwork necessary for continued collaborative growth for each of those entry points. Singletons will find clear instructions that fit their situation to help them connect with colleagues in their school or another school. Singletons in a PLC at Work will help singletons thrive as PLC practitioners, which will, in turn, lead to learning for all"--